A Nonlocal Model for Carbon Nanotubes under Axial Loads - Raffaele Barretta; Francesco Marotti de Sciarra (Advances in Materials Science and Engineering)
Various beam theories are formulated in literature using the nonlocal differential constitutive relation proposed by Eringen. A new variational framework is derived in the present paper by following a consistent thermodynamic approach based on a nonlocal constitutive law of gradient-type. Contrary to the results obtained by Eringen, the new model exhibits the nonlocality effect also for constant axial load distributions. The treatment can be adopted to get new benchmarks for numerical analyses.